Adenosine deaminase 2 produced by infiltrative monocytes promotes liver fibrosis in nonalcoholic fatty liver disease - Tiwari-Heckler, Shilpa; Yee, Eric U.; Yalcin, Yusuf; Park, Jiwoon; Nguyen, Duc-Huy T.; Gao, Wenda; Csizmadia, Eva; Afdhal, Nezam; Mukamal, Kenneth J.; Robson, Simon C.; Lai, Michelle; Schwartz, Robert E.; et al. (Cell reports, 2021)
Elevated circulating activity of adenosine deaminase 2 (ADA2) is associated with liver fibrosis in nonalcoholic fatty liver disease (NAFLD). In the liver of NAFLD patients, ADA2-positive portal macrophages are significantly associated with the degree of liver fibrosis. These liver macrophages are CD14- and CD16-positive and co-express chemokine receptors CCR2, CCR5, and CXCR3, indicating infiltrative monocyte origin. Human circulatory monocytes release ADA2 upon macrophage differentiation in vitro. When stimulated by recombinant human ADA2 (rhADA2), human monocyte-derived macrophages demonstrate upregulation of pro-inflammatory and pro-fibrotic genes, including PDGF-B, a key pro-fibrotic cytokine. This PDGF-B upregulation is reproduced by inosine, the enzymatic product of ADA2, but not adenosine, and is abolished by E359N, a loss-of-function mutation in ADA2. Finally, rhADA2 also stimulates PDGF-B production from Kupffer cells in primary human liver spheroids. Together, these data suggest that infiltrative monocytes promote fibrogenesis in NAFLD via ADA2-mediated autocrine/paracrine signaling culminating in enhanced PDGF-B production.
Gesehen am 13.12.2021